Microsatellite markers for Monitipora digitata designed using restriction-site associated DNA sequencing - Jia, Shuwen; Li, Yuanchao; Chen, Shiquan; Cai, Zefu; Shen, Jie; Wang, Yi; Wu, Zhongjie; Wang, Daoru (Frontiers in Marine Science, 2023)
Montipora digitata is a species belonging to the Acroporidae. In the Indo-Pacific region, M. digitata is widely distributed and is the dominant species of scleractinian coral in the South China Sea, however, there are currently no molecular markers suitable for assessing the species genetic diversity. Here, restriction-site associated DNA sequencing (RAD-seq) was used to isolate and characterize polymorphic microsatellite loci. A total of 317,361 RAD-tags were obtained using RAD-seq, including 6,778 microsatellite loci. Primer pairs for 106 loci were ordered and twenty-one polymorphic loci, that amplified reliably were identified. The number of alleles per locus were 2-7, observed heterozygosity was 0.111-0.556 with an average value of 0.285, and expected heterozygosity was 0.105- 0.802, with an average value of 0.536. Before Bonferroni correction 13 loci deviated significantly from the expectations of Hardy-Weinberg equilibrium (P < 0.05), after correction, two microsatellite loci deviated significantly (P < 0.0002). The polymorphic information content (PIC) ranged from 0.100-0.778, with 12 loci highly polymorphic (PIC > 0.5), six moderately polymorphic (0.25 < PIC < 0.5), and three loci with low polymorphism (PIC < 0.25). The microsatellite loci developed here will be effective tools for conservation genetic research on M. digitata.